МЕКТЕП БИЛИМЛЕНДИРИЎИ СЫПАТЫ ҲӘМ НӘТИЙЖЕЛИЛИГИН АСЫРЫЎ МӘСЕЛЕЛЕРИ - Нурланов, А. (ILIM hám JÁMIYET, 2020)
Education and upbringing work at school is directed to solving the main tasks – teaching responsibility, forming a personality in community. The article deals with some issues of increasing rffectiveness of the educational work in forming pupils' personality at general educational schools.